Optimization of cocoa nib roasting based on sensory properties and colour using response surface methodology - D.M.H. A.H. Farah; Zaibunnisa, A.H Zaibunnisa, A.H; Misnawi Jati (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2012)
Roasting of cocoa beans is a critical stage for development of its desirable flavour, aroma and colour. Prior to roasting, cocoa bean may taste astringent, bitter, acidy, musty, unclean, nutty or even chocolate-like, depends on the bean sources and their preparations. After roasting, the bean possesses a typical intense cocoa flavour. The Maillard or non-enzymatic browning reactions is a very important process for the development of cocoa flavor, which occurs primarily during the roasting process and it has generally been agreed that the main flavor components, pyrazines formation is associated within this reaction involving amino acids and reducing sugars. The effect of cocoa nib roasting conditions on sensory properties and colour of cocoa beans were investigated in this study. Roasting conditions in terms of temperature ranged from 110 to 160OC and time ranged from 15 to 40 min were optimized by using Response Surface Methodology based on the cocoa sensory characteristics including chocolate aroma, acidity, astringency, burnt taste and overall acceptability. The analyses used 9- point hedonic scale with twelve trained panelist. The changes in colour due to the roasting condition were also monitored using chromameter. Result of this study showed that sensory quality of cocoa liquor increased with the increase in roasting time and temperature up to 160OC and up to 40 min, respectively. Based on the Response Surface Methodology, the optimised operating condition for the roaster was at temperature of 127OC and time of 25 min. The proposed roasting conditions were able to produce superior quality cocoa beans that will be very useful for cocoa manufactures.Key words : Cocoa, cocoa liquor, flavour, aroma, colour, sensory characteristic, response surface methodology.